Cultural Adaptation of the MABC-2 Checklist as a Screening Tool for Developmental Coordination Disorder in Schools - Banátová, Kamila; Valtr, Ludvík; Cuberek, Roman (Occupational therapy in health care, 2023)
The purpose of this study was to adapt the MABC-2 Checklist to Czech primary schools by examining of its content validity and feasibility. The content validity achieved the satisfactory level in the second round of panels of experts on child motor development. The evidence on feasibility was obtained from classroom teachers who described this tool as clear, objective and having logical structure and its administration as comprehensible and fast. The MABC-2 Checklist is applicable instrument for the Czech school environment, but its adaptation to various countries should consider the items representing the common motor skills in local children.
Keywords: motorické dovednosti; školy; Checklist; Humans; Motor Skills Disorders; reprodukovatelnost výsledků; MABC-2 Checklist; motor assessment; Motor Skills; Developmental Coordination Disorder; poruchy motorických dovedností; ergoterapie; Schools; feasibility; lidé; Reproducibility of Results; kontrolní seznam; dítě; Child; Content validity; Occupational Therapy; primary school